PENGARUH PROFITABILITAS, PERTUMBUHAN ASET, UKURAN PERUSAHAAN, STRUKTUR AKTIVA DAN LIKUIDITAS TERHADAP STRUKTUR MODAL PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA TAHUN 2008 – 2010 - Verena Sari, Devi; Haryanto, A. Mulyo (Faculty of Economics and Business Diponegoro University, 2013)
There are some factors that influence the choice of capital structure of company. Some research has been done to know many factors that influence capital structure of company, such as profitability, business risk, stability of sales, asset growth, company size, tax, etc. There are often different result about those factors that influence capital structure especially profitability, asset growth, company size, asset structure, and liquidity. In 2008-2010 while capital structure of manufactures companies is increase, some variables is decrease, for example profitability.In 2008-2009 activa structure of manufactures companies is decrease, while capital structure is increase. In 2009-2010 activa structure is increase, while capital structure is also increase. It is not suitable with the research of Christianti (2006), Frank and Ghoyal (2007), and Harris and Raviv (1991). The population of this research is go public manufactures companies at BEI consist of 108 registered manufactures companies in Indonesia Capital Market Directory and having complete financial report for 4 years since 2007-2010. The method of data analysis that used in this research is regression analysis model, by testing the classic assumptions first.Based on the research is known that ROE, company size, and liquidity influence the capital structure of manufactures company in BEI from 2008-2010. While asset growth variable and asset structure does not influence the capital structure.